Managing the Uncertainties Inherent in Prohibitive Voice: How Leadership Interacts With Employee Political Skill - Wang, Xiaoxuan; Zhou, Fan (Frontiers in Psychology, 2021)
Drawing from uncertainty management theory, we examine how authoritarian leadership and humble leadership interact with employee political skill to predict prohibitive voice. We conducted a two-wave survey study of 43 managers and 176 subordinates in a power company in China. Our findings indicate that authoritarian leadership has less negative effect on the psychological safety of employees with higher political skill, which in turn leads to less negative effect on their prohibitive voice. Moreover, humble leadership is positively associated with prohibitive voice for employees with lower political skill. For employees with higher political skill, neither type of leadership behavior has a significant influence on their prohibitive voice. We outline the implications of these findings for both theory and managerial practices.